The Effectiveness of Physiotherapy and Complementary Therapies on Voice Disorders: A Systematic Review of Randomized Controlled Trials - Cardoso, Ricardo; Meneses, Rute F.; Lumini-Oliveira, José (Frontiers in Medicine, 2017)
The treatment of voice disorders includes physiotherapy and complementary therapies. However, research to support these treatments is scarce. Objective: to verify the effectiveness of physiotherapy and complementary therapies on voice disorders. Research on electronic databases Pubmed/Medline, SciELO and LILACS was performed using the combination: voice AND (treatment OR intervention) according to PRISMA guidelines. Only randomized controlled trials (RCTs) were included in the review. Studies were analyzed using the Physiotherapy Evidence Database (PEDro) scale and the Center for Evidence-Based Medicine’s Levels of Evidence scale. Eight papers met the inclusion criteria. From the RCTs included in this review, 6 assessed massage, 1 transcutaneous electrical nerve stimulation (TENS), 1 refer to spinal manipulative therapy and 1 to acupuncture. The literature regarding the effectiveness of physiotherapy and complementary therapies was good in both quality and results, indicating that massage, TENS and acupuncture seem to be effective treatments to reduce voice complaints and improve voice quality, supporting the inclusion of complementary therapies but mostly physiotherapy interventions in the treatment of patients with voice disorders.